Wymiary bezpieczeństwa międzynarodowego na szczytach G7/G8 - Matera, Rafał (Polityka i Społeczeństwo, 2021)
In the article the origins of G7 and G8 were briefly presented. The author also char-acterized the ways of functioning (called the system) of these groups. The main stress was put on the numerous issues of international security. Therefore the different dimen-sions of this were emphasized, and the commitments made by the leaders during yearly summits to solving the problems in this area were analyzed. At the end of the paper the author tried to answer the question if such a specific international institution is still able to act effectively to influence the different dimensions of international security in the new political situation (especially as a result of Russia’s foreign policy in 2014) .